Ultrasensitive determination for picomolar-level midecamycin in human serum by flow injection chemiluminescence using luminol–BSA system. Issue 6 (2011) - Lv Lv, Hairu Hairu; Tan Tan, Xijuan Xijuan; Zhang Zhang, Yun Yun; Song Song, Zhenghua Zhenghua
Abstract : An ultrasensitive method for determining picomolar midecamycin (MID) by flow injection (FI) chemiluminescence (CL) was first described based on the inhibitory effect of MID on luminol–BSA reaction. It was found that the CL intensity decrements were linear with the logarithm of MID concentrations in the range of 1.0–5000 pmol · l –1 with a detection limit as low as 0.3 pmol · l –1 (3σ). The relative standard deviation of seven repetitive measurements for 10 pmol · l –1 MID was 3.0%. At a flow rate of 2.0 ml · min –1, the whole analysis procedure including sampling and washing could be finished in 30 s, offering the sample efficiency of 120 h –1 . This proposed method was successfully applied to determine MID in human serum samples with the recoveries from 96.0 to 110.0%. The CL mechanism of luminol–BSA–MID reaction was also given.